ВЫРАЖЕННОСТЬ СИНДРОМА ИНТОКСИКАЦИИ У ДЕТЕЙ С РАЗЛИЧНЫМ ТЕЧЕНИЕМ ТУБЕРКУЛЕЗНОЙ ИНФЕКЦИИ - Яровая, Юлия Анатольевна; Мосина, Анна Владиславовна; Екимова, Виктория Романовна; Сацюк, Ирина Витальевна (FORCIPE, 2022)